Identifikasi Aksi Gen Epistasis pada Toleransi Kedelai terhadap Cekaman Aluminium - Sihaloho, Arvita Netti; ., Trikoesoemaningtyas; Sopandie, Didy; Wirnas, Desta (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
The efectiveness of selection depends on the gene action cotrolling the character. The presence of epistatic gene action will delay the genetic gain in self pollinated crops like soybean. The objective of this research was to obtain information on genetic control of soybean tolerance to aluminum toxicity on nutrient culture. This research was conducted at green house of the University Farm IPB Cikabayan, Bogor, from April to June 2013. This research used 120 seedlings of F2 population generated from crossing between Argomulyo (Al-sensitive) with Tanggamus (Al-tolerant). Seedlings were grown in nutrient culture for 14 days with Al concentration of 1.5 mM and pH 4.0, to observe the vegetative growth under aluminum stress condition. The result showed that mean of roots length, shoot length, shoot to root ratio, wet and dry weight of root and shoot exceeded both parents mean value with moderate to high heritability. All observed characters had continue distribution pattern, and controlled by many genes. Duplicate epistasis additive gene action controlled only root length while other characters were controlled by complementary epistasis gene action.Keywords: gene action, heritability, nutrient culture, selection, tocixity